Indonesia and ASEAN in Facing US-China Rivalry in the South China Sea to Create Regional Security Stability - Gerald Theodorus L. Toruan (GoAcademica Research & Publishing, 2021)
The South China Sea is a sea that has always attracted the attention of many countries in the world, in this sea there are two major countries in the world competition. The US and China are doing all they can to safeguard their respective national interests in these waters. The US and China are competing and tend to use a lot of military force. This rivalry will slowly threaten the stability of regional security. Indonesia, which has always been trusted by many countries to play an important role in efforts to keep the South China Sea safe from all forms of war, Indonesia, which is also an ASEAN member country, continues to emphasize that ASEAN will not be involved in one of the countries competing in the South China Sea. ASEAN together with Indonesia reminded the US and China to comply with existing international legal rules. This research is a qualitative research with data collection through in-depth interviews. The results of this study show that Indonesia and ASEAN play an important role in maintaining regional security stability. ASEAN cooperates with non-ASEAN countries such as America and China in the political, security, economic, social and cultural fields.